Eroticism developmental, cultural, and clinical realms - Akhtar, Salman 1946 July 31-; Gulati, Rajiv (Routledge, 2019)
"With contributions from distinguished scholars and clinicians who view human erotic desire from modern developmental, relational, societal, and cross-cultural perspectives, Eroticism: Developmental, Cultural, and Clinical Realms offers a multi-faceted and up-to-date glimpse into what we find sexually attractive and why. While psychoanalysis has unshackled itself from the narrow confines of instinct theory to include ego psychology, object relations theory, self psychology, and the contemporary relational paradigm, such heuristic and clinical advance is sorely needed to further our grasp of human eroticism and love. Accommodation also needs to be made for the cultural changes that have occurred over the last five or six decades. These include the feminist corrective to the phallocentrism of 'classical' psychoanalysis, the new insights into human subjectivity and personality development provided by the gay and lesbian movement, the contemporary de-centering of the essentialist and binary gender formulations, and the post-colonial voices of the non-Western people. By providing theoretically-anchored clinical guidelines, Eroticism provides not only an update on the early analytic understanding of human eroticism but advances clinical praxis as well"--